The pricing efficiency of equity warrants: a Malaysian case - Haron, Razali (ICFAI University Press, 2006)
The objective of this paper is to determine the pricing efficiency and behavior of equity warrants traded in the Bursa Malaysia. Specifically, this paper will focus on the studies of 85 randomly selected samples of listed warrants (46 main board warrants, while the remaining 39 were second board warrants) for the trading period of 100 days from January 1, 2004 until May 31, 2004. The model for pricing of warrants in this study is primarily based on the Black-Scholes Option Pricing Model (BSOPM). The theoretical price derived using the BSOPM will then be adjusted to incorporate the dilution effect. The adjusted theoretical pricing will afterward be compared with the actual market prices of warrants to determine the pricing efficiency. The paper will also look into related issues such as the extent of mispricing, factors that could lead to the inefficiencies, volatility of the warrants and the underlying stocks, the behavior of price relationships and appropriate strategies to be adopted with regards to the findings. The study concludes that there is significant mispricing on most of the traded warrants, which can be categorizes as underpriced, overpriced and extremely overpriced. A few warrants, nevertheless, were found to be insignificantly mispriced.